Xylem Parenchyma Anatomy and Gene Expression Patterns Indicate Mechanisms of Cavitation Resistance in Eucalyptus grandis During Drought - Rafael Keret; Paul N. Hills; David M. Drew (Plant-Environment Interactions, 2025)
ABSTRACT Tree survival under drought conditions depends on the ability to maintain functional xylem and avoid hydraulic failure due to cavitation. Although xylem parenchyma are key sites of metabolic activity in angiosperm wood, the anatomical and gene expression responses of this cell type to drought stress remain poorly characterized. This study investigated how Eucalyptus grandis W. Hill ex Maiden modifies parenchyma anatomy and gene expression under water deficit to enhance cavitation resistance. Under controlled drought conditions, plants produced significantly smaller ray parenchyma cells with increased frequency. This arrangement reduced the proportion of isolated vessels through elevated ray‐vessel contacts, likely enhancing solute delivery to stressed conduits. Transcriptomic analysis revealed upregulation of aquaporins, lipid transfer proteins, and enzymes involved in triacylglycerol biosynthesis, supporting roles in water transport and nanobubble stabilization under negative pressure. In parallel, genes associated with osmotic regulation, including various sugars, myo‐inositol, and metal ion transporters, were also induced, indicating putative solute‐mediated mechanisms for refilling embolized vessels. This transcriptomic response appears to be primarily triggered by oxidative and hypoxic stress signals. Collectively, these results indicate that xylem parenchyma contribute to embolism resistance by actively redistributing water and supporting hydraulic stability during drought. This work provides mechanistic insights into tree drought adaptation, with implications for forest management and climate resilience strategies.